Financial Retrenchment and Institutional Entrenchment: Will Legal Education Respond, Explode, or Just Wait it Out? A Clinician's View - Ian Weinstein (Washington University Journal of Law & Policy, 2013)
Both markets and ideas have turned against the American legal profession. Legal hiring has contracted, and law school enrollments are decreasing. The business models of big law and legal education are under pressure, current levels of student indebtedness seem unsustainable, and a hero has yet to emerge from our fragmented regulatory structures. In the realm of ideas, the information revolution has sparked deep critiques of structured knowledge and expertise, opening the roles of the law and the university in society to reexamination. We are less enamored of the scholar-lawyer and gaze with longing at technocrats. Thank you for this chance to speak about the role of clinical faculty in the new legal environment, which I take to be the world we will make, together, as we respond to market forces and new ideas. While my comments will necessarily advert to larger institutions and themes, my perspective is from one part (clinical faculty) of one sector (legal education) of what is, for most of us, our favorite complex social structure (law). I hope that clinical law faculty can lead and ease the transition to programs of legal education responsive to the new legal environment. Clinicians have supervised in a lot of different settings, and we know what works and how to return real value to law students. A well- structured clinical program integrates simulation, field placement, and in-house clinics to offer effective programs with reasonable efficiency. Clinicians have been experimenting with legal education for years and can help legal education meet the challenges of the new legal environment. I fear, however, that in a time of shrinking resources, some faculties and schools may become bogged down in contentious and ultimately counterproductive battles over how to allocate shrinking resources. In this version of the new legal environment, the status distinctions among law faculty could have real bite. Programs responsive to the expressed current needs of the bar and students could be sacrificed to programs controlled by better-entrenched faculty.
Keywords: legal education; clinical law faculty; clinical legal programs; new legal environment